Japanese patients with sporadic Hirschsprung: mutation analysis of the receptor tyrosine kinase proto-oncogene, endothelin-B receptor, endothelin-3, glial cell line-derived neurotrophic factor and neurturin genes: a comparison with similar studies - Sakai, T.; Nirasawa, Y.; Itoh, Y.; Wakizaka, A. (European journal of pediatrics, 2000)
We report on mutation analysis of five genes involved in the receptor tyrosine kinase (RET) or the endothelin-signalling pathways in 28 sporadic Japanese patients with Hirschsprung disease. Analysis of DNA obtained from peripheral blood cells revealed six mutations in the RET proto-oncogene, four of which were disease-causing mutations in exon 9 (D584G), the splice donor site of intron 10 (+2T to A), exon 11 (A654T), and exon 12 (T706A). A heterozygous A to G transition was found in 47 bases upstream from the 5' end of exon 2 in two HD patients but was also seen in one control subject (2/28; 1/24). A silent 2307T to G transversion was observed in exon 13. Two disease-causing mutations were detected in the endothelin receptor (EDNRB) gene, in the non-coding region of exon 1 (-26 G to A) and in exon 4 (A301T); the latter mutation was a novel one. One silent mutation was observed in exon 4 (codon 277). One heterozygous T to C mutation was found in the glial cell line-derived neurotrophic factor gene in 25 bases upstream of the coding region in exon 1. No nucleotide changes were detected in either the endothelin-3 or neurturin genes. Disease-causing mutation rates in the RET proto-oncogene and the EDNRB gene were estimated at 14.3% (4/28) and 10.7% (3/28), respectively. In addition to mutations in the RET and EDNRB genes, embryonic environmental factors and/or other genetic factors appear to be involved in the development of Hirschsprung disease. Further systematic studies of genetic variation in a large series of patients and controls are necessary for elucidating the pathogenesis of this disorder. This study provides further gene alterations as disease-causing mutations in Japanese cases of sporadic Hirschsprung disease. However, the low mutation rate of the susceptibility genes may indicate that Hirschsprung disease arises from a combination of genetic and environmental factors.